Analisis Jenis dan Penyebab Anemia Berdasarkan Kadar Hemoglobin dan Nilai MCV (Mean Corpuscular Volume) Pada Penderita Tuberkulosis Paru Baru Di Puskesmas Dasan Tapen - Nova Ramdhani, Iid Nirmala; Rohmi; Lalu Srigede; Agrijanti (Poltekkes Kemenkes Mataram, 2024)
Background: Tuberculosis is an infectious lung disease caused by Mycobacterium Tuberculosis which can cause several complications, including a decrease in hemoglobin levels, abnormal erythrocyte index values that can cause anemia. Examination of hemoglobin levels and MCV values to determine the type of anemia in tuberculosis patients. There are several types of anemia in tuberculosis patients and causes, one of which is microcytic anemia caused by a decrease in iron. Research Objective: Determine hemoglobin levels and erythrocyte index in patients with new pulmonary tuberculosis at Dasan Tapen Health Center Research Method: This study is observational analytic with Cross Sectional approach, the number of samples is 24 samples using the lomeslow formula with hemoglobin levels and MCV values. The collected data is then analyzed using descriptive tests. Results of the study: From 24 samples of tuberculosis patients as many as 5 people (21%) with a very mild degree of anemia, 16 (67%) people with a mild degree of anemia and 3 people (12%) with a moderate degree of anemia. A total of 18 people (75%) with microcytic type anemia and 6 (25%) people with normocytic type anemia. Conclusion: From 24 samples as many as 18 people (75%) with MCV values of <80 which indicates tuberculosis patients have microcytic anemia.